2014
DOI: 10.1007/s00467-014-2848-x
|View full text |Cite
|
Sign up to set email alerts
|

Early and frequent development of ocular hypertension in children with nephrotic syndrome

Abstract: Routine ophthalmologic examination should be conducted from the early phase after the start of prednisolone treatment. In addition, children with episodes of ocular hypertension may be at greater risk of its reappearance with relapse of the nephrotic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…19 However, another study in Japan found a higher prevalence of IOP (30.8%). 20 The retrospective cohort design of the Japan study, in contrast to our cross-sectional design, may have contributed to the higher prevalence. Studies on IOP in nephrotic children on long-term steroid therapy have been limited worldwide.…”
Section: Discussionmentioning
confidence: 83%
“…19 However, another study in Japan found a higher prevalence of IOP (30.8%). 20 The retrospective cohort design of the Japan study, in contrast to our cross-sectional design, may have contributed to the higher prevalence. Studies on IOP in nephrotic children on long-term steroid therapy have been limited worldwide.…”
Section: Discussionmentioning
confidence: 83%
“…Out of 12, nine studies are observational. Out of nine, two are retrospective cohort studies [30,33], five are prospective cohort studies [31,32,34,35,36], and one is both a retrospective and prospective cohort study [37]. Three studies out of 12 are case reports [27,28,29], and one is cross-sectional [26].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All included studies show prolonged steroid use followed by significantly high IOP/OHT development. The following studies also compared the dosage and duration of steroid use with IOP rise to see if any significant association exists between them [26,27,30,31,32,33,36,37]. The specific duration during treatment with steroids after which changes in IOP were detected is also discussed.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…(ii) Improvement: except for the occasional small amount of proteinuria, other indicators were normal for more than 3 years. (iii) Invalid: urine protein was still +++ (or higher) or death [15].…”
Section: Efficacy Evaluation Criteriamentioning
confidence: 99%